Late Glacial Sedimentation and History of the Lake Nipigon Basin, Ontario - Lemoine, Rick; Teller, James (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1995)
ABSTRACTThe Lake Nipigon basin lies north of the Lake Superior basin and was the hydrological link between glacial Lake Agassiz and the Great Lakes during part of the last deglaciation. A sequence of glaciolacustrine sediments, composed mainly of silt-clay rhythmites and sand, was deposited in the offshore waters of glacial Lake Nipigon by overflow from Lake Agassiz and meltwater from the retreating glacier margin. Sections from six long sediment cores and four lake bluff exposures reveal a sandy (early deglacial) lower section that is overlain by 300 to 850 silt-clay rhythmites (varves). Deposition of these varves, as well as coarser sediment along the western shore, began after 9200 BP, as the glacial margin retreated northward along the continental divide that separated the Nipigon basin from the higher Lake Agassiz basin to the west. The absence of ice rafted clasts in the rhythmites suggests that the ice had retreated from the lake by the time they were deposited. On the basis of their elevation in relation to the lowest raised beach at West Bay, which formed about 9000 BP, most rhythmites probably were deposited between 9000 and 8000 BP. Species of arboreal pollen are present in early postglacial sediments of the Nipigon-Superior lowlands, suggesting that the Lake Nipigon region became colonized by coniferous and deciduous forests soon after déglaciation. The presence of non-arboreal pollen species suggest that these forests were interspersed with open meadows and grasslands, similar to today's floral assemblages. Fossil molluscs recovered from glaciolacustrine sand exposed along the eastern side of the basin suggest that the limnological characteristics of late glacial Lake Nipigon were similar to those of today.